Heavy Metal Waste Using Ch/AgNPs Synthesized by Gamma Radiolysis: Preliminary Study - Ariyanti, D.; Basuki, K. T.; Megasari, K.; Ismail, I; Abimanyu, A.; Hamadi, H.; Rozana, K. (National Research and Innovation Agency, 2025)
Environmental issues had always been a problem for all countries in the world. Within a certain threshold, heavy metal waste in water and air must be considered. Various methods and instruments could be used for analysis of heavy metal waste levels. However, quick and accurate method needs to be upgraded in order to improve the efficiency of analysis. Ag nanoparticle is an alternative that could be used to detect the presence of heavy metal waste. Ag nanoparticles can be synthesized through reduction reaction with reductant agents from chemicals, biological compounds, and gamma irradiation. This research used qualilative analysis, utilizing chitosan stabilizer for Ag nanoparticles with gamma irradiation reductant in various doses, such as 7.5, 15, and 20 kGy. The results showed that AgNPs/chitosan was formed in the peak absorption range of 390-500 nm with optimum gamma irradiation dose of 15 kGy. In addition, AgNPs/chitosan has good sensitivity to detect Cr and Hg metals and was not sensitive to Cu and Pb metals.